Matienzo’s reflection on the theory of value and the organicist discursive topic - Vargas Silva, Fabián Azarías (2025)
This article addresses the problem of the extension and development of the philosophical commitments of Juan de Matienzo in his reflection on the theory of value. The main objective is to establish the relationship between Matienzo’s thought and the organicist discourse of the colonial thinkers of the Viceroyalty of Peru, between the sixteenth and eighteenth centuries. The methodology used is discourse analysis, approached from a hermeneutic approach. The main finding of the research consists in identifying and recognizing the philosophical assumptions of the common good and the metaphor of society as a body in the characterization of the estimation of economic value, according to the indigentia, considering it vain and misguided in certain cases. The article concludes by highlighting the contribution of the thinker from Valladolid to the historical debate on the nature of political power in the Viceroyalty of Peru, as well as the need to undertake a comprehensive philosophical investigation of Juan de Matienzo’s thought.